Multiple PDE5Is use as a marker of decreased overall men's health: A real-life study. - Davide Oreggia; Eugenio Ventimiglia; Paolo Capogrosso; Luca Boeri; Walter Cazzaniga; Filippo Pederzoli; Francesco Chierigo; Federico Dehò; Francesco Montorsi; Andrea Salonia (PLoS ONE, 2018)
Erectile dysfunction (ED) is considered a sentinel marker for poor general men's health status. Severe ED has been associated with poor response to phosphodiesterase type 5 inhibitors (PDE5Is) therapy. We sought to assess the association of multiple PDE5Is prescription with the overall patients' health status. Socio-demographic and clinical variables from 939 consecutive white-European, heterosexual, sexually-active men seeking medical help for ED at same tertiary-referral academic outpatient clinic were analyzed. Health-significant comorbidities were scored with the Charlson Comorbidity Index (CCI). Patients have been stratified into naïve and non-naïve according to their history of previous prescriptions of any PDE5I. Every patient completed the International Index of Erectile Function (IIEF) questionnaire. Logistic regression models tested the association between patients' baseline characteristics (thus including previous PDE5Is prescriptions) and the overall health status. Overall, 328 (35%) patients were non-naïve for PDE5Is. Of them, 172 (52%), 99 (30%), and 57 (17%) had been prescribed with 1, 2 or 3 different PDE5Is, respectively. Naïve and non-naïve patients did not differ in terms of age, BMI, baseline ED severity; conversely, non-naïve patients had a higher CCI score. At logistic MVA, the number of PDE5Is prescriptions emerged as an independent predictor of a higher burden of comorbidities regardless of ED severity; the higher the number of PDE5Is prescriptions, the higher the CCI score (OR 1.69, 2.49, and 2.90 for 1, 2 or 3 previous PDE5Is, respectively), after accounting for age, BMI, baseline ED severity and cigarette smoking. More than a third of patients seeking medical help for ED at a single tertiary-referral center were non-naïve for PDE5Is. The increasing number of previous prescriptions of PDE5Is emerged as a worrisome marker of a poorer overall men's health status regardless of ED severity.